Relationship of Competitive Anxiety and Mindfulness with Sports Self-Efficacy of Male Athletes Mediated by Family Cohesion - Aryan Hatami Gharibvand; Behnam Makvandi; Alireza Heidari (Shahid Bahonar University of Kerman, 2022)
Sports are generally competitive and stressful. Competitive sport anxiety in athletes affects sports self-efficacy. The present study aimed to investigate the relationship of competitive anxiety and mindfulness with sports self-efficacy of male athletes mediated by family cohesion. The statistical population of this descriptive-correlational study covered all male athletes in Masjed Soleyman, Iran in 2021, and a sample of 258 athletes was selected using convenience sampling. The research tools included the Sports Self-Efficacy Questionnaire, Competitive Sports Anxiety Questionnaire, the Mindfulness Inventory for Sport, and the Family Cohesion Questionnaire. The proposed model was evaluated using path analysis, and indirect correlations were tested with bootstrapping. The results suggested that all direct paths to sport self-efficacy were significant except athletic mindfulness (p<0.01), and indirect paths to sports self-efficacy became significant through family cohesion (p<0.01). According to the results of this study, the proposed model had good fitness and was a major step toward recognizing the factors affecting sports self-efficacy in male athletes as it can be helpful in designing effective plans to reduce males' experienced tension and improve their sports self-efficacy.